Electromagnetic properties of LaCa3Fe5O12 in the microwave range - Golenkina, V.V.; Ghyngazov, S.A.; Suslyaev, V.I.; Korovin, E.Yu.; Kuleshov, G.E.; Kaykenov, D.A.; Mustafin, E.S.; Mylnikova, T.S. (IOP Conf. Series: Materials Science and Engineering, 2016)
The X-ray diffraction analysis of the LaCa3Fe5O12 ferrite (lanthanum ferrite) prepared through high-temperature synthesis via ceramic technology was performed. It was found that ferrites belong to tetragonal system. The electromagnetic response from a flat layer of the composite based on this material under electromagnetic radiation in the frequency range of 0.01–18 GHz was investigated. It is shown that the developed material effectively interacts with electromagnetic radiation. The interaction effectiveness is directly proportional to ferrite concentration. Increased concentration of ferrite leads to growth of the reflection coefficient due to high conductivity of the material and visible decrease in the transmission coefficient in the frequency range of 4–14 GHz.
Keywords: Electromagnetic properties; LaCa3Fe5O12; microwave range